PENGARUH PERCEIVED BENEFITS, PERCEIVED VALUE, ATTRACTIVENESS OF ALTERNATIVES TERHADAP REPURCHASE INTENTION PADA JASA TRAVEL PT. CENDANA MITRA PERKASA CABANG SANGATTA - Ausy Riana; Ahmad Naharuddin (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2023)
The purpose of this study was to determinate the effect of perceived benefits, perceived vlue, and attractiveness of alternatives to PT. Cendana Mitra Perkasa, Sangatta. This research method uses primary data taken by distributing questionnaires to all respondents of Sandalwood Mitra Perkasa Sangatta and the factors used are quantitative methods. The population in this study was carried out directly in the Travel General Section of Trans Sandalwood Mitra Perkasa Sangatta. This study uses a questionnaire using an unknown formula, namely the Lemeshow formula. This study uses the SPSS version 25 application. To find out the research, the results are then entered into the classical assumption test, hypothesis testing, and instrument testing.